Day fines: European comparison and Czech malpractice - Drápal, Jakub (European journal of criminology, 2018)
Day fines are an expression of equality for rich and poor alike. Although the theoretical concept of day fines (also called unit or structured fines) has been thoroughly studied, there has not been any empirical study examining the link between the amount of one day fine and the wealth of an offender, to establish whether or not day fines in reality create equality between offenders with different levels of wealth. This paper reports a study conducted in the Czech Republic, which suggests that the concept of day fines does not function without a clear formula specifying how day fines should be calculated. A comparison of all states in Europe that use day fines indicates that only two states have such a formula. The other 20 states have no formula, and thus their propensity for misusing day fines may be high. Several other characteristics of day fines, such as the number of day fines issued and the conversion rate at which unpaid fines are transformed into days in prison, are also discussed.